2018
DOI: 10.1177/0022034518782141
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Innate Lymphoid Cell Populations in Gingival Tissue

Abstract: Innate lymphoid cells (ILCs) are a population of lymphocytes that act as the first line of immunologic defense at mucosal surfaces. The ILC family in the skin, lungs, and gastrointestinal tissues has been investigated, and there are reports of individual subsets of ILCs in the oral tissues. We sought to investigate the whole ILC population (group 1, 2, and 3 subsets) in the murine gingivae and the lymph nodes draining the oral cavity. We show that ILCs made up a greater proportion of the whole CD45+ lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…While these populations are more evident during periodontitis, they might also be part of the αβ T-cell population identified in the current work. Furthermore, innate lymphocyte cells (ILCs) also have been reported to reside in the gingiva (Brown et al 2018), and while we did not classify them, they are likely part of our unidentified leukocytes in both tissues. ILCs might also represent the IL-17Aproducing cells in our ex vivo stimulation studies since they were reported to secrete this cytokine in the oral mucosa (Sparber et al 2018).…”
Section: Discussionmentioning
confidence: 93%
“…While these populations are more evident during periodontitis, they might also be part of the αβ T-cell population identified in the current work. Furthermore, innate lymphocyte cells (ILCs) also have been reported to reside in the gingiva (Brown et al 2018), and while we did not classify them, they are likely part of our unidentified leukocytes in both tissues. ILCs might also represent the IL-17Aproducing cells in our ex vivo stimulation studies since they were reported to secrete this cytokine in the oral mucosa (Sparber et al 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Approximately 10–15% of total CD45 + cells identified were ILCs and most of them were IFN-γ secreting ILC1s (148). A recent study by Brown et al demonstrated the presence of all three groups of ILCs in the murine gingivae (149). ILC3s provided protection against oropharyngeal infection with Candida albicans through production of IL-17A and IL-17F induced by IL-23 (Figure 1) (72); thus, both Ror γ t −/− mice lacking ILC3s and mice depleted of ILC3s by antibody treatment suffered severe infection (72).…”
Section: Ilcs In the Oral Mucosamentioning
confidence: 99%
“…In the oropharyngeal cavity, murine ILC1s reside in salivary glands (Cortez et al, 2016) and gingiva (Brown et al, 2018), although ILC1 function in oral health and oral mucosal defense remains to be determined. To investigate the mechanisms underlying the resilience of the oral mucosa against viral infection, we established a murine model of viral oral mucosal infection using the poxvirus vaccinia virus (VACV).…”
Section: Introductionmentioning
confidence: 99%